The Effect of Audio Visual Media on Learning Outcomes of Grade IV Students In The Subject of Science - Sitohang, Shellyatika Muvela; Tambunan, Janwar; Sihombing, Lisbet Novianti (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the effect of the Picture And Picture learning model on the learning outcomes of fourth-grade students at UPTD SD Negeri 122353 Pematangsiantar. The research sample consisted of 24 students who were given 25 test items as research instruments, which were then tested for validity, reliability, discrimination index, and difficulty level. The test results showed that 20 items were valid with a reliability of 0.913, and most items had a moderate difficulty level with good to very good discrimination power. The study involved administering a Pre-Test, teaching material using the Picture And Picture model, followed by a Post-Test. The average Pre-Test score was 49.17 and increased to 83.13 in the Post-Test. Normality testing showed a normal distribution (sig = 0.16), and the t-test confirmed a significant effect of the learning model on student learning outcomes with a significance value of 0.000 and t-count (20.305) > t-table (7.634). Thus, the Picture And Picture learning model effectively improves the science learning outcomes of fourth-grade students at UPTD SD Negeri 122353 Pematangsiantar